Implementation of Electronic Student Worksheets with the Project-Based Learning (PjBL) model to Improve Motivation and Learning Outcomes - Tintin Kurniasih (Jurnal Ilmiah Pendidikan Fisika, 2022)
The purpose of this study was to determine the increase in motivation and learning outcomes by implementing electronic student worksheets with the Project-Based Learning (PjBL) model on the topic of physical and chemical changes in online learning in class VII-E of SMP Negeri 14 Banjarmasin. The research method used is Classroom Action Research. The research was carried out in 2 cycles: action planning, implementation, observation, and reflection. Data sources come from teachers and students through observation, tests, non-tests, and document review. The data analysis technique used is quantitative analysis. The questionnaire results on the learning motivation of class VII-E SMP Negeri 14 Banjarmasin in the I cycle was 23.33%, and the II cycle was 63.33% in the high category. Furthermore, the student learning outcomes test results for class VII-E SMP Negeri 14 Banjarmasin in the I cycle, 56.67% completed learning, and 43.33% did not complete learning. While in the II cycle, 86.67% finished studying, and 13.33% did not. Based on the results of this study, it can be concluded that the application of electronic worksheets with PjBL on the topic of physical and chemical changes in online learning in class VII-E of SMP Negeri 14 Banjarmasin in the 2020/2021 academic year can increase student motivation and learning outcomes. Therefore, the electronic student worksheets with the model (PjBL) can be chosen as an alternative to online and offline learning to increase motivation and learning outcomes.